354 Surgical Proforma Done by Surgical Doctors; Clinical Audit. (19th August 2022) - Al-Ghazawi, M; Toquero, L; Li, M; Pauk, T
Abstract: Aim: To improve the clerking performed by all surgical grades at our Trust and to prevent any implication might happen in case the clerking was insufficient such as medical errors, delay in treatment and poor quality of data for future research and audits. Method: Two cycle audit in which the first cycle analysed one hundred fully randomized surgical entries for completeness of all aspects of history, examination & plan over two months in 2021. Then new surgical proforma was applied and used for all patients thereafter. Subsequently, second cycle performed later, and same randomization was applied. Results: Whereas fully completed proformas compromised only 4% of all entries in first cycle, this percentage increased by more than six-fold to reach 26% in second one. Both history of present illness and physical exam showed the major improvement. Even though some sections such NEWS score and social history kept showing small, completed percentage, it was slightly higher than in the first cycle. 69% was the total improvement across all sections between two cycles. Conclusion: New surgical proforma applied at our hospital improved the clerking done by surgical doctors and hence improved the care provided to patients in first place and served as a very rich environment to future research and Audits.